Influence of Transformability on the Formation of Superinfection Double Lysogens in Haemophilus influenzae - Stuy, Johan H. (1971)
Superinfection of growing (nontransformable) cells of defectively lysogenic strains of Haemophilus influenzae with wild-type or with mutant phage HP1 resulted in a number of double lysogens and a small number of monolysogens with altered prophage. The double lysogens were identified by analysis of their monolysogenic segregants and by examining their deoxyribonucleic acid in certain test crosses. The results indicate that the majority had been formed by insertion of the infecting phage genome within the resident prophage. Superinfection of transformable bacteria gave rise to cells with altered prophages (presumably transformants) and to double lysogens which had gained or lost wild-type prophage loci.